Field-tuning mechanisms of spin switching and spin reorientation transition in praseodymium-erbium orthoferrite single crystals - Ma, Xiaoxuan; Yuan, Ning; Yang, Wanting; Zhu, Shuang; Shi, Chenfei; Song, Huan; Sun, Zhiqiang; Kang, Baojuan; Ren, Wei; Cao, Shixun (Inorganic chemistry, 2022)
Field-tuning mechanisms of spin switching and spin reorientation (SR) transition were investigated in a series of high-quality single crystal samples of PrxEr1-xFeO3 (x = 0, 0.1, 0.3, 0.5) prepared using the optical floating zone method. The single crystal quality, structure, and axis orientation were determined by room-temperature powder X-ray diffraction, back-reflection Laue X-ray diffraction, and Raman scattering at room temperature. Magnetic measurements indicate that the type and temperature region of SR transition are tuned by introducing different ratios of Pr3+ doping (x = 0, 0.1, 0.3, 0.5). The trigger temperatures of spin switching and magnetization compensation temperature of PrxEr1-xFeO3 crystals can be adjusted by doping with different proportions of Pr3+. Furthermore, the trigger temperature of the two types of spin switching in Pr0.3Er0.7FeO3 along the a-axis can be regulated by an external field. Meanwhile, the isothermal magnetic field-triggered spin switching effect is also observed along the a and c-axes of Pr0.3Er0.7FeO3. An in-depth understanding of the magnetic coupling and competition between the R3+ and Fe3+ magnetic sublattices, within the RFeO3 system, has important implications for advancing the practical applications of the relevant spin switching materials.
Gesehen am 18.10.2022